Developing Finite Element Methods for Simulating Transformation Optics Devices with Metamaterials (Communications in Computational Physics, 2018)
In this paper, we first develop the mathematical modeling equations forwave propagation in several transformation optics devices, including electromagneticconcentrator, rotator and splitter. Then we propose the corresponding finite elementtime-domain methods for simulating wave propagation in these transformation opticsdevices. We implement the proposed algorithms and our numerical results demonstratethe effectiveness of our modeling equations. To our best knowledge, this is thefirst work on time-domain finite element simulation carried out for the electromagneticconcentrator, rotator and splitter.